2017
DOI: 10.1007/s10753-017-0640-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Periodontitis in the Potentialization of the Effects of Immobilism in the Skeletal Striated Muscle

Abstract: This study aims to evaluate if ligature-induced periodontitis can potentiates the deleterious effects of immobilization in the skeletal striated muscle, contributing to the development of muscle atrophy due to disuse. Forty Wistar rats were divided into four groups: (1) Control Group (CG), (2) Periodontal Disease (PDG), (3) Immobilized (IG), and (4) Immobilized with Periodontal Disease (IPDG). Periodontal disease was induced for 30 days, with ligature method, and the immobilization was performed with cast band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…1 ). Interaction between frailty, obesity, and muscle strength is important in an aging population and is also related to periodontitis and tooth loss [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Interaction between frailty, obesity, and muscle strength is important in an aging population and is also related to periodontitis and tooth loss [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that the association between periodontal disease and immobilization promoted potentiation of muscle fibre area reduction and augmentation of connective tissue. No studies were found relating these factors to the anterior tibial muscle; however, Leite et al [5], in the same association model, found that there were morphological alterations of muscle fibres and an increase in the connective tissue of the soleus muscle, confirming that the association of both increases the harmful effects of immobilization in muscle tissue, regardless of the structure and molecular composition of the muscles.…”
Section: Discussionmentioning
confidence: 98%
“…A similar result was found by Kuntz et al [16] in a model with in the area, but there was reduction of the smallest diameter. This may have occurred because periodontal disease may induce a systemic inflammatory response, thus favouring the reduction of muscle fibre [5,24], which may have occurred due to synergy between oxidative stress, inflammatory cytokines and disuse, so that atrophy was accelerated or aggravated since, according to Fink et al [25] immobilization and inflammation decrease muscle strength, with the combination of both factors becoming additive. In the present study, muscle strength was not compared, but changes in fibre diameter and increase in the number of nuclei, as well as the increase of inflammatory cells in the association of the two conditions, evidences the need to control diseases that lead to systemic inflammation when associated with immobilism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations